The Methodological going near establishment of objective terms of application of khozyaystvenno-pravovoy responsibility for offence in the field of competition - Корчак, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article grounds methodological possibility of consideration of financial or formal signs of offences inthe field of competition at establishment of objective terms of application of khozyaystvenno-pravovoy responsibility.